Association of immune-inflammation indexes with incidence and prognosis of diabetic nephropathy: a systematic review and meta-analysis - Wang, Yijue; Liu, Yan; Gu, Wenling; Cai, Boyu; Lei, Min; Luo, Yingyu; Zhang, Nannan (Frontiers in Endocrinology, 2025)
IntroductionThe significance of immune-inflammation indexes in diabetic nephropathy (DN) was assessed in this meta-analysis to offer guidance for clinical diagnosis and treatment for DN.MethodsWe performed a meta-analysis on the association between immune-inflammation indexes and the incidence and prognosis of DN, specifically focusing on the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI). We thoroughly searched PubMed, Web of Science, Embase, and Cochrane from inception to September 2024. The statistical analysis was performed using R 4.2.3 software.Results56 studies were ultimately included, comprising 50 that examined the association between DN incidence and immune-inflammation indexes and 8 that examined the association between DN prognosis and immune-inflammation indexes. The levels of NLR, MLR, PLR, and SII were significantly higher in DN patients than in non-DN ones. Besides, high NLR, MLR, SII, and SIRI were associated with elevated incidence of DN. Moreover, the high NLR group was more prone to a poor prognosis than the low NLR group (OR: 1.372, 95% CI: 1.160-1.624).ConclusionsImmune-inflammation indexes can, to a certain extent, serve as a biomarker to predict the occurrence of DN. In addition, high NLR has a potential association with the occurrence of poor prognosis in DN.